2008
DOI: 10.1093/tropej/fmn107
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Preterm/Very Low Birth Weight Care in Nigeria

Abstract: The care of very low birth weight (VLBW) neonates may impose an enormous burden on professional resources and finances of caregivers. This study seeks to evaluate the immediate cost of care of VLBW babies in a developing economy. Twenty-four hospital case records VLBW babies who survived till discharge over a 1 year period at the University College Hospital, Ibadan, Nigeria were reviewed. Estimates of the out of pocket costs of managing these babies were calculated. The overall cost of hospital care ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 11 publications
2
35
1
1
Order By: Relevance
“…The cost of managing ELBW infants varies between developed and developing countries and different regions within a country 4,6,15,16 17 . In the South African study 14 , mean duration of mechanical ventilation was 8.08 days and the mean duration of supplemental oxygen was 8.2 days in VLBW babies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of managing ELBW infants varies between developed and developing countries and different regions within a country 4,6,15,16 17 . In the South African study 14 , mean duration of mechanical ventilation was 8.08 days and the mean duration of supplemental oxygen was 8.2 days in VLBW babies.…”
Section: Discussionmentioning
confidence: 99%
“…The cost varies greatly between developed countries and developing countries and between different centres within a country or a region as it largely depends on the cost of sophisticated and advanced neonatal care and the cost of the health care system in general [4][5][6][7][8] . Consequently, it is difficult to compare the cost among different centres.…”
Section: Introductionmentioning
confidence: 99%
“…[20,[23][24][25]50] The highest number of articles published in a given year (n = 7) was in 2008, and the number of studies peaked from 2007 to 2009 (figure 2). There was an average of 3.68 years (SD 2.47; range [1][2][3][4][5][6][7][8][9][10][11] between the year of publication of the study and the last year of data collection.…”
Section: Extent and Trend Of Health Economic Studiesmentioning
confidence: 99%
“…Tongo et al, [24] Henshaw et al, [29] 2008 Cost analysis Tx of abortion-related complications Women who had an abortion outside hospital paid more for tx (NGN13 900) than those who went directly to the hospital for an abortion (NGN3800) or those treated for miscarriage (NGN5100)…”
Section: Extent and Trend Of Health Economic Studiesmentioning
confidence: 99%
“…Increases in morbidity related to low birth weight (LBW) contributes to high direct medical costs, 2528 non-medical costs such as higher child care expenses, 29 and less tangible costs such as the burden of caregiving to families. 30,31 Recent studies using national data sets have identified linkages between general LHD spending and broad, distal mortality outcomes and related disparities. 32,33 Based on these studies and another indicating that MCH-specific services provided by LHDs are linked to reductions in mortality disparities, 2 this study used unique, detailed data obtained through a two-state consortium of Public Health Practice-Based Research Network (PBRN) partners to examine impacts of MCH-related spending by LHDs on birth outcomes.…”
Section: Introductionmentioning
confidence: 99%